Relevansi Konsep Kafaah Dalam Pemilihan Pasangan Hidup : Perspektif Mahasiswi Arab Universitas Al Azhar Mesir - Nurul Azizah, Muadzah (Kartika: Jurnal Studi Keislaman, 2025)
The concept of kafaah (compatibility or equality) in Islamic jurisprudence serves as a foundational principle to maintain marital harmony by ensuring balance between prospective spouses in religious, social, and economic aspects. However, contemporary social transformations and the growing participation of women in education and public life have reshaped the interpretation and application of kafaah, particularly in Egyptian society. This study aims to analyze the relevance and transformation of kafaah in modern contexts through the perspectives of Arab female students at Al-Azhar University, Egypt. Employing a qualitative approach, the research utilizes in-depth interviews with two participants Afnan (Shafi‘i school) and Aya (Hanafi school) to explore their views on kafaah in selecting a life partner. The findings indicate that while kafaah remains essential, its meaning has shifted from emphasizing social and economic status toward moral integrity, character, and shared responsibility. Afnan considers financial readiness and stable employment sufficient for marriage, while Aya emphasizes higher economic stability and social preparedness, including home ownership, jewelry (shabka), and completion of military service. The study concludes that kafaah has evolved from a marker of social legitimacy into a moral framework that reinforces equality and mutual responsibility in the formation of modern Islamic families